The Effectiveness of Lavender Aromatherapy on Reducing Pain Intensity in The First Stage of Labor Active - Skania, Pratiwi Cahya; Halimatusyadiah, Leni; Jamilah, Jamilah (Jurnal Biologi Tropis, 2024)
Pregnant woman looks forward to the moment she gives birth in order to experience the joy she longs for. if the baby, placenta, and amniotic membranes leave the mother's uterus at term (after 37 weeks) without complications, the process is considered normal. At TPMB Siti Hapsah, S.Tr.Keb in 2024, the purpose of this study is to determine whether lavender aromatherapy reduces pain intensity during the active phase of first stage labor. The Quasy Experiment research method is used in this quantitative research design. This study used a one-group pretest-posttest design with 32 respondents. The Wilcoxon test was used to analyze the observation sheet data. Lavender aromatherapy was found to be effective at reducing pain intensity during the active phase of first stage labor at TPMB Siti Hapsah, s.Tr.Keb in 2024 because the obtained result had a significance value of 0.000, which was lower than the significance result of 5% (p-value = 0.000  0.05). During the initial active phase of labor, lavender aromatherapy is recommended for use as a complementary therapy.